The Safe Harbour Program – a bridge between the European and American systems of personal data protection - Zygmunt, Justyna (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2014)
The article is devoted to a comparison of the American and European systems of data protection and the transfer of personal data from the European Union to the United States of America. The author outlines the problems and then analyzes the regulations in order to identify differences between the two systems. Then, based on the previous considerations, she assesses the effectiveness of the Safe Harbour Program, which was set up to serve as a tool to facilitate the transfer of personal data. The article ends by providing information about the directions of policy changes and work on the new EU Regulation on the protection of personal data.